The Implementation of Bilingual Education at Singaraja Montessori School - Sugiani, Ni Nyoman; Budasi, I Gede; Ramendra, Dewa Putu (Yayasan Payungi Smart Madani, 2025)
Bilingual education has become increasingly prominent in Bali, driven by the rapid growth of globalization and tourism. This study explores the implementation of bilingual education at a Montessori school, focusing on its application in the classroom, the benefits perceived by teachers, and the challenges encountered. Employing a qualitative research design, data were gathered through classroom observations, semi-structured interviews, and document analysis. Three teachers were selected as participants using purposive sampling. The instruments used included observation checklists, interview guides, and note-taking protocols, with data analyzed through qualitative content analysis. The findings indicate that the school integrates both the Montessori and Merdeka curricula, applying Content and Language Integrated Learning (CLIL) and translanguaging strategies. A strong bilingual education model is adopted by the teachers. Reported benefits include enhanced language proficiency, improved career prospects, increased intercultural awareness, and the enrichment of pedagogical practices. However, several challenges were also identified, such as restrictive school policies, varying teacher backgrounds, and entrenched academic culture. This study contributes to the growing body of knowledge on bilingual education in non-Western, multicultural contexts by providing empirical evidence on curriculum integration and bilingual instructional strategies. It offers practical insights for policymakers, school leaders, and educators seeking to implement or refine bilingual programs, particularly in regions influenced by tourism and globalization. Furthermore, it highlights the need for institutional support and professional development to overcome systemic and pedagogical challenges in bilingual teaching environments.